2002
DOI: 10.2337/diacare.25.12.2302
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-DQ Genotype in Autoantibody-Negative and Rapid-Onset Type 1 Diabetes

Abstract: OBJECTIVE—Some type 1 diabetic patients have a distinct phenotype characterized by the absence of pancreatic autoantibodies and fulminant clinical symptoms at onset, including marked hyperglycemia, severe diabetic ketoacidosis, and normal to near-normal HbA1c levels with complete destruction of β-cells. However, little is known about genetic factors of this distinct subtype of diabetes (fulminant autoantibody-negative type 1 diabetes). RESEARCH DESIGN AND METHODS—We analyzed HLA-DQ genotypes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 24 publications
6
41
0
Order By: Relevance
“…Analysis of the allelic combination of HLA-DR-DQ has shown that homozygotes with DR4-DQ4 exhibit a greater effect than heterozygotes with DR4-DQ4 regarding predisposition to fulminant diabetes. These findings coincide with small pilot studies, which were performed independently of this study [21,22]. These findings also suggest that HLA-DR4 and/or DQ4 could play an important role in the development of fulminant type 1 diabetes.…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of the allelic combination of HLA-DR-DQ has shown that homozygotes with DR4-DQ4 exhibit a greater effect than heterozygotes with DR4-DQ4 regarding predisposition to fulminant diabetes. These findings coincide with small pilot studies, which were performed independently of this study [21,22]. These findings also suggest that HLA-DR4 and/or DQ4 could play an important role in the development of fulminant type 1 diabetes.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, in this issue of Diabetes, Endo et al (10) report that 5 out of 15 patients with AIP were heterozygous for the HLA DRB1* 0405-DQB1*0401 haplotype, which confirms previously published results in a Japanese population (11,12). It is noteworthy that a recent study provided convincing evidence that CD4…”
supporting
confidence: 73%
“…On the other hand, the frequency and OR of the DRB1*04:05-DQA1*03:03-DQB1*04:01 haplotype in fulminant T1D are higher than those of the DRB1*04:05-DQA1*03:03-DQB1*04:01 haplotype in rapid-onset T1D. The DR9 haplotype is less frequent in fulminant T1D than in rapid-onset T1D and does not confer susceptibility to fulminant T1D Tanaka et al, 2002).…”
Section: Hla Class II Genes and T1d In The Japanese Populationmentioning
confidence: 88%
“…are the most frequently observed susceptibility haplotypes in the Japanese (Awata et al, 1992;Kawabata et al, 2002;Kobayashi et al, 1993;Maruyama et al, 1994;Murao et al, 2004;Tanaka et al, 2002;Yasunaga et al, 1996). However, studies conducted before the discovery of fulminant T1D may have included patients with fulminant T1D.…”
Section: Hla Class II Genes and T1d In The Japanese Populationmentioning
confidence: 99%
See 1 more Smart Citation